Determinan kualitas laba - Tampubolon, Tamara Cheryll; Rondonuwu, Sintje (Manajemen Bisnis dan Keuangan Korporat, 2024)
The company's ability to survive in the pandemic era is an important consideration for investors when making an investment. This ability can be assessed based on the profit quality signal provided by the company. Earnings quality can be influenced by various factors, including profit growth, company size, and company life cycle. This research is aimed for looking at the influence of profit growth, company size, and company life cycle on profit quality. The objects studied in this research are IDX 30 or the 30 most fundamental companies on the Indonesian Stock Exchange. This type of research is quantitative research with a total sample of 13 companies. It is concluded that earnings growth has a significant negative influence on earnings quality, while company size has no influence on earnings quality, and the company life cycle has a significant negative influence on earnings quality.